Analisis Semiotika Visual Dan Makna Pada Logo “Sampoerna Retail Community” - Iqbal Lukman; Heldi Heldi (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
Nowadays, logos have become a form of choice for conveying communication. The logo has become a center of information for the community, but based on the author's interviews with several people related to the community, they have not optimally understood the meaning of the visual Sampoerna Retail Community logo, therefore the author is interested in researching it. The objectives of the research are 1. Know and describe the visuals of the Sampoerna Retail Community logo. 2. Analyze and describe the visual meaning contained in the Sampoerna Retail Community logo. The research method uses descriptive qualitative. With Charles Sanders Pierce's semiotic analysis approach. Through analytical steps, we explore the meaning behind the Sampoerna Retail Community logo: icon, index, symbol and meaning. The results of this research provide an illustration that Sampoerna Retail Community is trying to display its logo by prioritizing the spirit of providing the best service to the community by using icons, indexes, symbols and meanings that are appropriate to display to the public and consumers. The results of the researchers found that there are six visual parts contained in the Sampoerna Retail Community logo. There are six meanings, namely: 1. A place and location for shopping. 2. A woven logogram with the nature of mutual cooperation. 3. The color red symbolizes enthusiasm. 4. The color white symbolizes purity and comfort. 5. SRC text fosters a modern feel. 6. Close means being everywhere, thrifty means affordable prices, friendly means friendly and welcoming. This is what the public needs to know.